Fabrication of promising competitive graphene nanocomposite transducer to determine Prucalopride succinate in pharmaceutical formulation and in spiked human biological fluids - Marwa T. Saad; Shereen A. Boltia; Taghreed A. Fattah; Hala E. Zaazaa (BMC Chemistry)
Abstract The development of a newly fabricated ion-selective electrode (ISE) solid-contacted type for the determination of prucalopride succinate represents a significant advancement in analytical chemistry, particularly in the context of green chemistry principles. The optimization process involved numerous trials to ensure the selection of a cation exchanger and ionophore that offer high sensitivity and selectivity for prucalopride succinate. Through these optimization trials, sodium tetrakis was identified as the most suitable cation exchanger, while calix [8] arene demonstrated the highest affinity towards prucalopride succinate as the ionophore. This careful selection of components ensures accurate and specific detection of prucalopride succinate. To enhance the electroanalytical performance of the ISE, a graphene nanocomposite layer was developed as an ion-electron transducer between the carbon and synthetic polymeric membrane. This graphene-nanocomposite layer improves the overall performance of the ISE, providing a Nernstian slope of 57.249 mV per decade, which aligns with the recommendations of the International Union of Pure and Applied Chemistry (IUPAC). The integration of these components and the utilization of green chemistry principles in the design of the fabricated ISE enable rapid and accurate determination of prucalopride succinate. This innovative approach holds great potential for applications in pharmaceutical analysis and quality control, providing a more sustainable and efficient method for the analysis of prucalopride succinate.